Analisis Dinamika Komunikasi Virtual Pada Mahasiswa Universitas Pancasakti Tegal di Roblok: Pendekatan Sosial Penetration Theory - Lutri Bunga Lestari; Arini Okta Ramadanti; Ike Desi Florina (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The development of digital technology has positioned online games as new spaces for virtual communication, particularly among university students. Roblox functions not only as an entertainment platform but also as a virtual social environment where interpersonal relationships are formed. This study aims to analyze the dynamics of virtual communication among students of Universitas Pancasakti Tegal on Roblox using the Social Penetration Theory approach. A qualitative descriptive method was employed, with data collected through in-depth interviews, virtual observation, and documentation. Informants were selected using purposive sampling, focusing on active students who regularly play Roblox and engage in in-game communication. The findings reveal that students’ virtual communication on Roblox develops gradually in accordance with the stages of Social Penetration Theory, namely orientation, exploratory affective exchange, affective exchange, and stable exchange. Initial interactions are functional and superficial through text chat, which later evolve into more personal communication via voice chat and external platforms as trust and comfort increase. However, not all interactions reach deeper stages due to inhibiting factors such as toxic behavior and privacy concerns. This study highlights Roblox as a virtual communication space that facilitates the formation of interpersonal relationships within the metaverse context.